Dakwah Islam Melalui Karya Sastra - Nurhayati, Enung; Junaedi, Dedi; Sahliah, Sahliah (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2019)
The Da'wah through literary works is based on Al-Quran surah Ali Imran verse 110. Da'wah through literary works, in this case, the writer or creator of literary works is an element of da'i. Religious points, both religious themes or messages are elements of the message of preaching. While literary works are the media of his da'wah. Da'wah through literary works will be most successful depending on the way the presentation and packaging it uses. Da'i who are competent to become Islamic writers are needed. This was to meet the challenges when many writers (writers) often turned away from religious literature and preferred to pursue liberalism or genital literature (exploiting sex). Therefore, a cadre of the preachers should be needed for proselytizing professionals through literary works. Need to conduct training based on